2013
DOI: 10.1002/jor.22458
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measures of damage to subchondral bone are associated with functional outcome following treatment of displaced acetabular fractures

Abstract: Current analysis of displaced acetabular fractures is limited in its ability to predict functional outcome. This study aimed to (1) quantify initial acetabular damage following acetabular fracture through measurement of subchondral bone density and fracture lines, and (2) evaluate associations between acetabular damage and functional outcomes following fracture. Subchondral bone intensity maps were created for 24 patients with unilateral acetabular fractures. Measures of crack length and density differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The same authors have demonstrated that the superior acetabular region and the posterior wall have the highest bone density in the acetabulum (Fig. 3) [16]. Today, three-dimensional CT scanning greatly facilitates the surgeon’s understanding: 1) insight into the importance of the fracture relative to the critical zones of the acetabulum (the roof and the posterior wall, as discussed above), 2) visualizing fracture planes to facilitate reduction and establish orthogonal screw fixation.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…The same authors have demonstrated that the superior acetabular region and the posterior wall have the highest bone density in the acetabulum (Fig. 3) [16]. Today, three-dimensional CT scanning greatly facilitates the surgeon’s understanding: 1) insight into the importance of the fracture relative to the critical zones of the acetabulum (the roof and the posterior wall, as discussed above), 2) visualizing fracture planes to facilitate reduction and establish orthogonal screw fixation.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…The peroneal division of the sciatic nerve is usually invariably injured, though less frequently the tibial division is as well. A foot drop will occur if the peroneal nerve division of the sciatic nerve is injured 23,24 . The surgical exposure and reduction of acetabular fractures may become more straightforward and practical with the improved method because it was closer to the acetabular quadrilateral plate 11,25 .…”
Section: Discussionmentioning
confidence: 99%
“…It can be used to develop a new classification system or sub-classifications of existed classification systems based on real fracture patterns and comminution zones [8]. Fracture prognosis prediction, hardware placement, and implant design optimization can also benefit from the use of fracture map [8][9][10]. In the past decade, the fracture heat map technique has been applied to scapular fracture [11], tibial pilon fracture [7], radial head fracture [12], and tibial plateau fracture [8], etc.…”
Section: Introductionmentioning
confidence: 99%